Structural organization of mammalian prions as probed by limited proteolysis. - Ester Vázquez-Fernández; Jana Alonso; Miguel A Pastrana; Adriana Ramos; Lothar Stitz; Enric Vidal; Irina Dynin; Benjamin Petsch; Christopher J Silva; Jesús R Requena (PLoS ONE, 2012)
Elucidation of the structure of PrP(Sc) continues to be one major challenge in prion research. The mechanism of propagation of these infectious agents will not be understood until their structure is solved. Given that high resolution techniques such as NMR or X-ray crystallography cannot be used, a number of lower resolution analytical approaches have been attempted. Thus, limited proteolysis has been successfully used to pinpoint flexible regions within prion multimers (PrP(Sc)). However, the presence of covalently attached sugar antennae and glycosylphosphatidylinositol (GPI) moieties makes mass spectrometry-based analysis impractical. In order to surmount these difficulties we analyzed PrP(Sc) from transgenic mice expressing prion protein (PrP) lacking the GPI membrane anchor. Such animals produce prions that are devoid of the GPI anchor and sugar antennae, and, thereby, permit the detection and location of flexible, proteinase K (PK) susceptible regions by Western blot and mass spectrometry-based analysis. GPI-less PrP(Sc) samples were digested with PK. PK-resistant peptides were identified, and found to correspond to molecules cleaved at positions 81, 85, 89, 116, 118, 133, 134, 141, 152, 153, 162, 169 and 179. The first 10 peptides (to position 153), match very well with PK cleavage sites we previously identified in wild type PrP(Sc). These results reinforce the hypothesis that the structure of PrP(Sc) consists of a series of highly PK-resistant β-sheet strands connected by short flexible PK-sensitive loops and turns. A sizeable C-terminal stretch of PrP(Sc) is highly resistant to PK and therefore perhaps also contains β-sheet secondary structure.